System Capacity - Velez, Fernando J. (2010)
In Fixed WiMAX, the contribution from each transmission mode can be incorporated into an implicit formulation to obtain the supported throughput as a function of the carrier-to-interference ratio. This is done by weighting the physical throughput in each concentric coverage ring by the size of the ring. In this paper, multi-hop cells are formed by a central coverage zone and three outer coverage zones served by cheaper low-complexity relays. It is assumed that line of sight propagation to the bases station is achieved in a high percentage of the cell, reducing the impact of selective fading, through allowing dimensioning to be done by GIS cellular planning tools. By using tri-sectorised equipment there is a need for three times more bandwidth, while hardware costs are higher. In our proposal for relays, the FDD mode is considered and the frames need to guarantee resources for BS-to-MS communications but also for BS-to-RS and RS-to-MS communications. These requirements leads to a 1/5 asymmetry factor between the UL and DL in the omnidirectional BS case and to a 3/7 asymmetry factor in the case of tri-sectored BSs. Although the reuse distance is augmented by a factor, we show that with the use of relays in FDD mode only the consideration of tri-sectored BSs with reuse pattern K = 3 (at the cost of extra channels, corresponding to 9 channels) enables to obtain values for the throughput comparable to cases without the use of relays. The presence of sub-channelisation only improves the results for the highest values of R. The consideration of tri-sectored BS antennas with K = 1 (whilst keeping the number of required channels – equal to 3) did not enable to obtain values of the throughput comparable to the ones without using relays, although frame format is more favourable. Relays can be cheaper than BS with full functionalities. As the use of relays may lead to lower costs it is worthwhile to analyse the impact of using them on costs and revenues.